Prototype Pengontrolan Lampu Dengan Menggunakan Ponsel Pintar Android Via Wifi Berbasis Mikrokontroler - Ahyo, tur -; Rahmad, Muh. Prasuci; Imansyah, Nur (ELKHA : Jurnal Teknik Elektro, 2020)
Everyone must have a rush outside the house, sometimes in a hurry even forget to turn off and turn on the light in the house during the morning or night. At times like this, of course, that makes people lazy to go back to the house to turn off the light that causes electricity waste and make time efficient to turn on the light. In this study a prototype of lighting control will be made where observations have been made about the prototype need. Then look for literature related to light control prototypes. The prototype method uses the blynk application as a light controller connected to the internet with the media via wifi. ESP-01 as a microcontroller processes commands from a smart phone which then results in controlling both the off and on the lights as well as the receiver and transmitter in the lighting control system. Thyristor switch module as an electrical switch instead of a manual switch at home to turn on or turn off the light through commands from the microcontroller. This prototype is very easy to use because through a prototype smart phone can be controlled, so this is a solution for humans to turn on or turn off the light by utilizing wifi in the house. From the experiments that have been carried out the average speed of the prototype tool receives an order from open source blynk application in 0.28 seconds